Jolly and Less Jolly Challenges in Working on the Norwegian-Lithuanian Dictionary - Griškevičienė, Aurelija (Scandinavistica Vilnensis, 2014)
The Norwegian-Lithuanian Dictionary is a joint project of lexicographers from the universities of Vilnius and Oslo. The dictionary consists of approximately 48,000 entries. It is initially intended as a paper dictionary, but as it is compiled in XML, an electronic version is also planned for the future. The dictionary is bidirectional: that is, it is intended for native speakers of both Norwegian and Lithuanian, and it provides information on both the source language (Norwegian) and the target language (Lithuanian).The aim of the article is to give a presentation of the project, point out innovative aspects of the project, and analyse the jolly (expected) and less jolly (unexpected) challenges we faced in the two main stages of compiling the dictionary. In the first stage we adapted a base from another bilingual dictionary (the Large Norwegian-Russian Dictionary), reusing its lemma list and information on the source language, Norwegian. In the second stage we created a conception and a system for information on the target language, Lithuanian, and (perhaps for the first time in Lithuanian bilingual lexicography) included several types of information for non-native users of Lithuanian.
Keywords: lexicography; bilingual dictionaries; Norwegian-Lithuanian Dictionary